Phenolic-rich extracts of Teucrium oliverianum confer protection against thioacetamide-induced liver fibrosis in rats: Insights from metabolomics, biochemical and histopathological analysis - Rania F. Ahmed; Abdelbaset M. Elgamal; Heba A. S. El-Nashar; Noha A. Mowaad; Rania Elgohary; Mohamed A. El-Saied; Mohamed A. Farag; Hiroshi Imagawa; Abdelsamed I. Elshamy; Ahmed M. Abd-ElGawad (PLoS ONE, 2025)
Background Hepatic fibrosis unfolds as a pathological buildup of extracellular matrix triggered by liver injury. Thioacetamide (TAA) plays a versatile role across various fields—from industrial processes and laboratory research to chemical stabilization. Teucrium plants, widely traditional plants, owing to its myriads of pharmacological activities. Methods and findings T. oliverianum ethanolic (TO-EtOH) and ethyl acetate (TO-EtOAc) extracts were explored for their bioactive metabolites via UHPLC-ESI-qTOF-MS/MS that yielded 48 compounds, mainly flavonoids and phenylethanoid glycosides, alongside phenolic acids, iridoid glycosides, and limonoids. Both extracts showed notable hepatoprotective effects in a thioacetamide (TAA)-induced liver injury model, supporting their therapeutic potential. The TAA group showed a significant increase in AST, ALT, ALP, MDA and TNF-α levels concurrent with a significant decrease of GSH level versus normal control group. In contrast, TO-EtOAC and TO-EtOH administered rats showed a decrease in liver enzymes, including ALT, AST, ALP, total bilirubin, and MDA, and an increase in GSH as compared to the TAA model group. Furthermore, both extracts considerably decreased the overall liver TNF-α content inferring anti-inflammatory action. The histo- and immunohistochemical assays of liver tissue of rats in TAA revealed prominent pathological alterations with bridging fibroplasia in multiple hepatic lobules. A restorative effect that improved hepatic morphology with apparent normal hepatic cells and nominal fibroplasia was evident in the administration of both extracts. Among both extracts, TO-EtOH appeared more effective than TO-EtOAC as manifested by a significant improvement in liver’s biochemical parameters and structural organization. Conclusion This study provides robust evidence supporting the antifibrotic effects of T. oliverianum in a TAA-induced liver injury model. The anti-proliferative activity and hepatoprotective effects are likely to be mediated by its richness in phenolic acids, flavonoids and phenylethanoids.